Periodization of the history of ethnographical study of Tuvans - Irgit, Choduraa K. (The New Research of Tuva, 2013)
Article puts forward a general periodization of the history of ethnographical research of Tuvans showing the development of researchers’ cognitive and scientific interest and the overall dynamics of publications about Tuva and Tuvans from the beginning of the 17th century to the present time.
Keywords: Tuvans’ ethnographics; periodization; history; expeditions to Tuva; ethnographical tuvinology; interdisciplinary